2021
DOI: 10.3390/ijms22168726
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria, Cyanotoxins, and Neurodegenerative Diseases: Dangerous Liaisons

Abstract: The prevalence of neurodegenerative disease (ND) is increasing, partly owing to extensions in lifespan, with a larger percentage of members living to an older age, but the ND aetiology and pathogenesis are not fully understood, and effective treatments are still lacking. Neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis are generally thought to progress as a consequence of genetic susceptibility and environmental influences. Up to now, several enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 155 publications
0
26
0
Order By: Relevance
“…The amyloid cascade hypothesis, which dominated the field for about 30 years, suggested that the accumulation of amyloid β (Aβ) is a primary factor responsible for the pathological alterations [5]. Alternative hypotheses proposed other possible AD initiating factors, such as metabolic imbalance, infections, and toxins [2,6,7]. These factors, together with Aβ peptides and other proteins with altered conformation, affect several neurotransmitters and growth factors-dependent signaling pathways and communication networks between neurons, microglia, astrocytes, and other cells, leading to synaptic apoptosis and neuronal death.…”
Section: Introductionmentioning
confidence: 99%
“…The amyloid cascade hypothesis, which dominated the field for about 30 years, suggested that the accumulation of amyloid β (Aβ) is a primary factor responsible for the pathological alterations [5]. Alternative hypotheses proposed other possible AD initiating factors, such as metabolic imbalance, infections, and toxins [2,6,7]. These factors, together with Aβ peptides and other proteins with altered conformation, affect several neurotransmitters and growth factors-dependent signaling pathways and communication networks between neurons, microglia, astrocytes, and other cells, leading to synaptic apoptosis and neuronal death.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo and in vitro evidence has suggested a link between the ingestion of BMAA and the development of the amyotrophic lateral sclerosis-parkinsonism-dementia complex, a neurodegenerative disease that was described for the first time in the indigenous people of Guam. Supplementation with L-serine would be of interest in those cases of ALS where there is suspicion of environmental contamination by cyanobacteria [49,51,52,53]. In addition, as we said above, the amount of L-serine and ROS regulates the plastic metabolic response by p53 in muscle [36,37].…”
Section: L-serine Amino Acidmentioning
confidence: 97%
“…These deaths could not be attributed to hepatotoxicity due to the rapidity of their occurrence, and they were most likely due to the many copies of pro-apoptotic genes such as TP53 that they have in their genomes. In addition, such mammals have many skeletal muscle fibers-some of these animals were elephants [51,52,53,54].…”
Section: 4mentioning
confidence: 99%
“…Manual work, especially when it includes the creation of commodities, has been linked to an increased risk of clinical Alzheimer's disease [31]. There are also studies about risk factors, pathogenesis, and structural and functional changes associated with neurodegeneration in AD [32][33][34], the genetic, clinical, and biochemical data of individual patients [35], searching for peripheral biomarkers in neurodegenerative diseases [36] and gut microbiota regulation and their implication in the development of neurodegenerative disease [37,38]. In [39], the pathophysiological basis and biomarkers of AD pathology, and molecular signs of neural inflammation in neurodegenerative diseases are investigated.…”
Section: Introductionmentioning
confidence: 99%